OOAD-BASED MONITORING INFORMATION SYSTEM IN SOFTWARE PRODUCTION MAKING IN PT. XYZ - Shedriko, Shedriko; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
Abstract PT. XYZ is a company engaged in making software that involves both the owner and employees in their activities. This privately-owned company operation includes the functions of project managing, system analysis to programming with work ranging from receiving proposals, collecting user requirements documents, design, user acceptance tests to deployment. The overall function of the work requires centralized overall monitoring where inputting can be done by many people while the management can be carried out by certain personnel only. The research methodology used is descriptive based on object-oriented analysis and design. The results of this study are the design of information systems based on object-oriented analysis and design that are ready to use in their implementation into the program code. The results are expected to be used by PT. XYZ and other companies engaged in similar services in monitoring projects that are in progress